Couvade Syndrome: Origin, Characterization, and Frequency. (1st June 2022) - Sá Couto, J.; Pão Trigo, M.; Da Luz, B.; Rodrigues, J.; Ventura Gil, T.
Abstract : Introduction: The word couvade originated from the French verb couver, meaning to hatch, nest, or brood. Custom of Couvade or Couvade Syndrome (CS) is a poorly understood phenomenon observed since ancient times, in which the expectant father experiences somatic and psychological symptoms of pregnancy. Objectives: Defining what is CS. Identifying possible origin. Hypothesizing causes. Identifying CS frequency. Methods: PubMed database search, with "Couvade syndrome" keyword expression. Seven articles were selected among the best matches. Reference lists of articles were reviewed to identify additional articles. Results: Currently, there are several views on this phenomenon, including religious, cultural, medical, psychoanalytic, and psychological. CS is used in Psychiatry to describe somatic symptoms resembling pregnancy and/or childbirth in expecting fathers, such as weight gain, diarrhea or constipation, toothache, and headache. Lipkin and Lamb (1982) studied 300 couples from New York: they diagnosed Couvade Syndrome in 22, 5% of fathers. Nevertheless, Brennan et al. (2007) found different incidence rates of CS diagnose in different areas of the world: 20% in Sweden; 25–97% in United States; 61% in Thailand; 68% in China; 35% in Russia. Conclusions: Whether CS constitutes a disease entity, or it should be considered a ritual or custom remains a matter of debate. Different rates of CS around the globe may indicate that culture plays an important role. It may be a way for fathers-to-be to cope with changes imposed by pregnancy in the mother and in the couple. Overall, it is a fascinating intersection between the physiological and psychological realms. Disclosure: No significant relationships.